Teaching Arabic By The Method Of Almana In The Dialogue An Applied Study - Omar Abu Al-Majd Husain Kassem Mohamad (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
The method of almana (translated as “prevent”) is a method of dialogue based on presenting the evidence and arguments and knowing the reasons behind the authenticity or faultiness of the conversation. The objective of the research is the method of almana of the primer Arabic literature, that is, the Quran. The research methodologies relied upon in conducting the present study are analytical and inductive methods, which help to collect the examples of almana from the Quran, classify them, and identify the associations of arguments with each other and the implications. The results of the research, which are the rationalist used the method of (almana) in discussions and dialogues, does not make it forbidden to look into this method and search for it in the texts of the Quran and the Sunnah, provided that it does not distort the texts. The method of almana is based on the evidence and arguments, whether with a definitive statement or with the idea that presents the solution to a problem. It came in easy sentences whose meanings are not hidden but for non-scholars. The Qur’anic method of almana is distinguished by using the most appropriate and the most required forms for the statement of the truth using brief sentences as it is very effective to achieve the objectives of the dialogue and its results are seen. Hence, the Qur’anic method of almana doesn’t contain digressions and numerous introductions that lengthen the conversation and miss the guidance and main objectives of the verses. The topics in which the method of almana was used varied, and the research showed that it was used in several issues related to creeds, such as the oneness of Allah, the prophethood of Muhammad, and the resurrection, in addition to ethical issues.